2018
DOI: 10.1111/sdi.12745
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in hemodialysis: Causative mechanisms, clinical implications, and possible therapeutic interventions

Abstract: Oxidative stress (OS) is the result of prooxidant molecules overwhelming the antioxidant defense mechanisms. Hemodialysis (HD) constitutes a state of elevated inflammation and OS, due to loss of antioxidants during dialysis and activation of white blood cells triggering production of reactive oxygen species. Dialysis vintage, dialysis methods, and type and condition of vascular access, biocompatibility of dialyzer membrane and dialysate, iron administration, and anemia all can play a role in aggravating OS, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
103
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 174 publications
(324 reference statements)
1
103
0
5
Order By: Relevance
“…Increased oxidative stress and reduced serum Mg levels in CKD patients have been associated with uremia and several factors associated with the HD procedure, such as composition of DFs. [9,11,16]. Owing to the positive impact of citrate containing fluids on the hemodynamic parameters and redox status of HD patients, it has recently been proposed to use citrate, instead of the less physiologic acetate, in DFs to improve the outcome of HD process in clinical practice [16,35].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Increased oxidative stress and reduced serum Mg levels in CKD patients have been associated with uremia and several factors associated with the HD procedure, such as composition of DFs. [9,11,16]. Owing to the positive impact of citrate containing fluids on the hemodynamic parameters and redox status of HD patients, it has recently been proposed to use citrate, instead of the less physiologic acetate, in DFs to improve the outcome of HD process in clinical practice [16,35].…”
Section: Discussionmentioning
confidence: 99%
“…These uremic toxins, represented by IS, is extremely toxic and difficult to eliminate by conventional dialysis; consequently, high IS levels may trigger oxidative-inflammatory stress, playing a key pathophysiologic role in CKD. In fact, several studies have confirmed that the occurrence of CVD induced by CKD is closely related to the IS accumulation [3].Uremia promotes a state of enhanced oxidative stress, which is the result of pro-oxidant molecules, such as reactive oxygen species (ROS), overwhelming the antioxidant defense mechanisms [9]. An increase in oxidative stress occurs during the dialysis session owing to the loss of antioxidants (e.g., uric acid, etc.)…”
mentioning
confidence: 99%
See 3 more Smart Citations